2017
DOI: 10.1007/s11255-017-1700-1
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of renal transplantation on cognitive function in hemodialysis patients: a longitudinal study

Abstract: ESKD patients have impaired CF as documented by prolonged P300 latencies. There was normalization of P300 latencies post-transplantation indicating role of uremic toxins in CF impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Intradialytic cerebral blood flow decline has correlated with ultrafiltration volumes and a measurable decline in executive function. This persists in those who remained on dialysis but not those who undergo renal transplant ( 49 , 50 ). Compared to patients on PD, HD patients have worse cognitive function and higher rates of dementia ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intradialytic cerebral blood flow decline has correlated with ultrafiltration volumes and a measurable decline in executive function. This persists in those who remained on dialysis but not those who undergo renal transplant ( 49 , 50 ). Compared to patients on PD, HD patients have worse cognitive function and higher rates of dementia ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive function has been reported to improve with KTx; Chhabra et al [ 100 ] conducted a study measuring P300 in 20 KTx recipients aged 18–50 years before and 3 months after KTx. They demonstrated that P300 latency, which was prolonged before KTx, shortened to a level comparable to healthy subjects after KTx, and reported that cognitive function improved with an improvement in anemia.…”
Section: Measures For CI In Patients With Ckdmentioning
confidence: 99%